2017
DOI: 10.1155/2017/5204639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Precursor Concentration on Structural Optical and Electrical Properties of NiO Thin Films Prepared by Spray Pyrolysis

Abstract: Undoped nickel oxide (NiO) thin films were deposited on 500 ∘ C heated glass substrates using spray pyrolysis method at (0.015-0.1 M) range of precursor. The latter was obtained by decomposition of nickel nitrate hexahydrate in double distilled water. Effect of precursor concentration on structural, optical, and electrical properties of NiO thin films was investigated. X-ray diffraction (XRD) shows the formation of NiO under cubic structure with single diffraction peak along (111) plane at 2 = 37.24 ∘ . When p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…4 (e) and Fig. 4 In relation to the summations made in Section 3.2, it is better understood that the observed grain growth in the pH2 and pH3 grown CdTe layers is an indication of a reduction in the lattice defects, resulting in a reduction in both the internal strain ε and dislocation density δ [25]. Another improvement in the characteristic properties of CdTe layers after CCT has been captured in numerous literature [26], [27].…”
Section: Morphological and Compositional Studymentioning
confidence: 75%
“…4 (e) and Fig. 4 In relation to the summations made in Section 3.2, it is better understood that the observed grain growth in the pH2 and pH3 grown CdTe layers is an indication of a reduction in the lattice defects, resulting in a reduction in both the internal strain ε and dislocation density δ [25]. Another improvement in the characteristic properties of CdTe layers after CCT has been captured in numerous literature [26], [27].…”
Section: Morphological and Compositional Studymentioning
confidence: 75%
“…Among these methods, sputtering has been considered due to the lack of sample contamination, high process speed, film uniformity, and accuracy of work, and so on (Haji Abdolvahab et al, 2020). Nickel oxide (NiO) is one of the metal oxides that have been used from the past to the present, which is one of the materials used in the manufacture of electronic components such as transistors due to its high sensitivity, high electron transfer speed, low cost (Barir et al, 2017; Majd et al, 2017; Majd et al, 2018). Nickel oxide is a p‐type semiconductor with a NaCl‐like structure that has a bandgap in the range of 3.6‑4 eV (Akinkuade et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The coloration efficiency and cycle stability of NiO films depend on the film thickness [14][15], temperature [16][17], concentration [5,[18][19][20], preparation techniques [21], etc. Among these, the preparation with different conditions of the precursor significantly affects the morphology, thickness, optical, and electrochromic properties.…”
Section: Introductionmentioning
confidence: 99%
“…This result demonstrated that as nickel chloride concentration increased from 0.05 M to 0.10 M, the optical contrast value increased, and then the optical contrast value decreased when nickel chloride increased. Rafia B. et al [20] studied the synthesized nickel oxide film by spray pyrolysis with varied solutions of nickel nitrate hexahydrate [Ni(NO3)2⸳6H2O]. NiO films showed the transmittance value had decreased when solutions of nickel nitrate hexahydrate were increased.…”
Section: Introductionmentioning
confidence: 99%